Dynamics of Photoinduced Energy Transfer in Fully and Partially Conjugated Polymers Bearing π-Extended Donor and Acceptor Monomers - Kim, Youngseo; Kwon, Na Yeon; Park, Su Hong; Cho, Min Ju; Choi, Dong Hoon; Park, Sungnam (Frontiers in Chemistry, 2020)
The photophysical properties of donor (D)-acceptor (A) polymers were studied by designing two types of polymers, (D-σ-A)n and (D-π-A)n, with non-conjugated alkyl (sp3) and π-conjugated (sp2) linkers using -extended donor and acceptor monomers that exhibit planar A-D-A structures. The non-conjugated alkyl linker provides structural flexibility to the (D-σ-A)n polymers, while the π-conjugated linker retains the rigid structure of the (D-π-A)n polymers. Photoinduced energy transfer occurs from the large donor to acceptor units in both polymers. However, the photoinduced energy transfer dynamics are found to be dependent on the conformation of the polymers, where the difference is dictated by the types of linkers between the donor and acceptor units. In solution, intramolecular energy transfer is relatively favorable for the (D-σ-A)n polymers with flexible linkers that allow the donor and acceptor units to be proximally located in the polymers. On the other hand, intermolecular (or interchain) energy transfer is dominant in the two polymer films because the -extended donor and acceptor units in polymers are closely packed. The structural flexibility of the linkers between the donor and acceptor repeating units in the polymers affects the efficiency of energy transfer between the donor and acceptor units and the overall photophysical properties of the polymers.